Raptors vs aliens: can indigenous birds of prey help control invasive predators?. Issue 2 (3rd April 2017) - Glen, A. S.; Pech, R. P.; Davey, C.; Molsher, R. L.
ABSTRACT: Apex predators often have strong effects on populations of prey, and other predators. Research on predator interactions has mostly focused on closely related assemblages, especially carnivorous mammals, but strong interactions can also occur between distantly related predators. We investigated dietary overlap and intraguild predation between invasive foxes ( Vulpes vulpes ) and native wedge-tailed eagles ( Aquila audax ) in eastern Australia. Eagles consumed large numbers of foxes, and dietary overlap between the two species suggested potential for competition if food is limiting. We posit that conserving native raptors could reduce the environmental and economic impacts of invasive predators. We suggest ideas for further research in Australia and New Zealand, where the impacts of invasive predators have been particularly severe.